Combined effect of interventions with pure or enriched mixtures of (poly)phenols and anti-diabetic medication in type 2 diabetes management: a meta-analysis of randomized controlled human trials: review - Raimundo, Ana F. (2020)
Purpose: (Poly)phenols have been reported to confer protective effects against type 2 diabetes but the precise association remains elusive. This meta-analysis aimed to assess the effects of (poly)phenol intake on well-established biomarkers in people with type 2 diabetes or at risk of developing diabetes. Methods: A systematic search was conducted using the following selection criteria: (1) human randomized controlled trials involving individuals with prediabetes and type 2 diabetes; (2) one or more of the following biomarkers: glucose, glycated haemoglobin (HbA1c), insulin, pro-insulin, homeostatic model assessment of insulin resistance (HOMA-IR), islet amyloid polypeptide (IAPP)/amylin, pro-IAPP/pro-amylin, glucagon, C-peptide; (3) chronic intervention with pure or enriched mixtures of (poly)phenols. From 488 references, 88 were assessed for eligibility; data were extracted from 27 studies and 20 were used for meta-analysis. The groups included in the meta-analysis were: (poly)phenol mixtures, isoflavones, flavanols, anthocyanins and resveratrol. Results: Estimated intervention/control mean differences evidenced that, overall, the consumption of (poly)phenols contributed to reduced fasting glucose levels (- 3.32 mg/dL; 95% CI - 5.86, - 0.77; P = 0.011). Hb1Ac was only slightly reduced (- 0.24%; 95% CI - 0.43, - 0.044; P = 0.016) whereas the levels of insulin and HOMA-IR were not altered. Subgroup comparative analyses indicated a stronger effect on blood glucose in individuals with diabetes (- 5.86 mg/dL, 95% CI - 11.34, - 0.39; P = 0.036) and this effect was even stronger in individuals taking anti-diabetic medication (- 10.17 mg/dL, 95% CI - 16.59, - 3.75; P = 0.002). Conclusions: Our results support that the consumption of (poly)phenols may contribute to lower glucose levels in individuals with type 2 diabetes or at risk of diabetes and that these compounds may also act in combination with anti-diabetic drugs.